Polysaccharides From Chrysanthemum morifolium Ramat Ameliorate Colitis Rats via Regulation of the Metabolic Profiling and NF-κ B/TLR4 and IL-6/JAK2/STAT3 Signaling Pathways - Tao, Jin-Hua; Duan, Jin-Ao; Zhang, Wei; Jiang, Shu; Guo, Jian-Ming; Wei, Dan-Dan (Frontiers in Pharmacology, 2018)
Previous studies have indicated that polysaccharides extracted from Chrysanthemum morifolium Ramat could prominently ameliorate colitis rats, but its possible mechanism remains unclear. In this study, the underlying mechanism of chrysanthemum polysaccharides was explored by the metabolic profiling analysis and correlated signaling pathways. TNBS/ethanol induced colitis was used to investigate the intervention efficacy after oral administration of Chrysanthemum polysaccharides. The levels of cytokines such as TNF-α, IFN-γ, IL-6 and IL-1β, and the activities of SOD, MPO, and MDA were determined. We also performed western-blot for p65, TLR4, p-JAK2 and STAT3 protein expressionin the colon tissue to probe their mechanisms of correlated signaling pathways. What’s more, the metabolic changes in plasma and urine from colitis rats were investigated based on UPLC-Q-TOF/MS combined with MetabolynxTM software. The potential biomarkers and metabolic pathway were also tentatively identified.The metabolic profiles of plasma and urine were clearly improved in model rats after oral administration of chrysanthemum polysaccharides. Thirty-two (seventeen in serum and fifteen in urine) potential biomarkers were identified. The endogenous metabolites were mainly involved in linoleic acid, retinol, arachidonic acid, glycerophospholipid and primary bile acid metabolism in plasma, and nicotinate and nicotinamide, ascorbateandaldarate, histidine and β-alanine metabolism in urine. After polysaccharides intervention, these markers turned back to normal level at some extent. Meanwhile, the elevated expression levels of pp65, TLR4, p-STAT3 and p-JAK2 were significantly decreased after treatment.Results suggested that chrysanthemum polysaccharides would be a potential prebiotics for alleviation of TNBS-induced colitis. The study paved the way for the further exploration of the pathogenesis, early diagnosis and curative drug development of the colitis.